Associations between alcohol use expectancies and drinking problems among French soldiers (Swiss Medical Weekly, 2015)
AIMS: The aim of the study was to evaluate which alcohol use expectancies could predict harmful use in the French Army to explore some hypotheses concerning socialising or coping effects. METHODS: A cross-sectional survey, using self-administered questionnaires, was conducted in two Army units in 2011 (n = 249). Hazardous alcohol use and dependence were screened using the Alcohol Use Disorders Identification Test (AUDIT). Alcohol expectancies were measured with the Alcohol Effects Questionnaire (AEFQ). A cluster analysis was performed to identify AEFQ dimensions in our sample. Relationships between AUDIT and AEFQ were explored using multinomial logistic regression. RESULTS: According to AUDIT, 46.6% of soldiers used alcohol without hazard, 26.1% had hazardous use without dependence and 18.1% had use with dependence. The AEFQ had an adequate internal coherence with a 0.78 α coefficient. The scales identified by the cluster analysis in our sample fitted those retained in the originally validated AEFQ, with a correspondence ranging from 60% to 100%. In multivariate analysis, the scale “Social and physical pleasure” was associated with increasing hazardous use and subjects who scored higher on “Global positive” and “Social and physical pleasure” scales were more at risk of dependence. CONCLUSION: The present study, in line with previous research in terms of importance of alcohol use disorders among military personnel, found that alcohol use expectancies are associated with alcohol misuse among soldiers. This could suggest underlying coping mechanisms towards stress that have to be further explored.